"The party of power": authoritarian diaspora and pluralism by default in Ukraine. Issue 3 (3rd April 2021) - Way, Lucan Ahmad
ABSTRACT: This article seeks to explain why Ukraine maintained a competitive electoral regime despite the dominance of authoritarian diaspora in the decades after the country became independent in 1991. The anti-democratic effect of the diaspora was significantly mitigated by the fact that it was not organized into a political party and split by longstanding regional divisions. Because of their disorganization and dispersion across the political spectrum, old Soviet elites possessed limited capacity to consolidate power. The result was "pluralism by default" in which democratic politics emerged out of authoritarian weakness. At the same time, variation in the (dis)organization of different authoritarian diaspora networks partially explains divergent levels of political competition between different Ukrainian governments in the 1990s and early 2000s.